The Safety of Soft Contact Lenses in Children - Bullimore, Mark A (Optometry and vision science, 2017)
There is increasing interest in fitting children with soft contact lenses. This review collates data from a range of studies to estimate the incidence of complications, specifically corneal infiltrative events and microbial keratitis, in patients under the age of 18 years. Peer-review papers were identified using PubMed and the Web of Science. A broad range of studies are summarized including large-scale epidemiological studies of contact lens-related complications, hospital-based case series, long- and short-term prospective studies, and multicenter retrospective studies. Nine prospective studies representing 1800 patient years of wear in 7- to 19-year-olds include safety outcomes. In three large prospective studies representing between 159 and 723 patient years of soft contact lens wear in patients 8 to 14 years, the incidence of corneal infiltrative events is up to 136 per 10,000 years. Data from a large retrospective study show similar rates of corneal infiltrative events: 97 per 10,000 years in 8- to 12-year-olds (based on 411 patient years of wear) and 335 per 10,000 years in 13- to 17-year-olds (based on 1372 patient years of wear). None of the prospective studies report any cases of microbial keratitis. Five clinical studies where safety data are not reported constitute a further 493 patient years. One retrospective study found no cases of microbial keratitis occurred in 8- to 12-year-olds (411 patient years) and an incidence of 15 per 10,000 patient years in 13- to 17-year-olds (1372 patient years)-no higher than the incidence of microbial keratitis in adults wearing soft contact lenses on an overnight basis. The overall picture is that the incidence of corneal infiltrative events in children is no higher than in adults, and in the youngest age range of 8 to 11 years, it may be markedly lower.